The effect of communication and motivation on employee performance at PT. Transdata Satkomindo Medan - Damanik, Ivan Diego Tua; Sihombing, Devi Sartika; Sinaga, Garbiella Dwi Oktaviani; Hutasoit, Rachel Yemima; Siregar, Melinda (International Journal for Educational and Vocational Studies, 2022)
This study aims to see the results of the analysis of the influence of communication and motivation on employee performance at PT. Transdata Satkomindo Medan. Research conducted at PT. Transdata Satkomindo Medan Kec. Medan Sunggal, Medan City, North Sumatra, 20122 which will take place on July 15, 2021 until its completion. The research population is all the employees of the PT, totaling 37 employees and the sample used is a total sampling of all 37 employees. Test the research hypothesis using Multiple Linear Regression with 3 variables. The results of the descriptive statistical data analysis were obtained for the communication value with an average of 31.7 and the standard deviation of 2.33. Then the work motivation variable obtained an average value of 27.7 with a standard deviation of 1.77. The results of the t test are obtained, namely the communication T count is smaller than T table (0.202 < 1.30) with a significance level of 0.8> 0.05. Then on work motivation obtained the value of T count < T table (-1.39 < 1.30). it means that the two variables have a negative and insignificant effect.